Cracking behavior of sea sand RC beam bonded externally with CFRP plate - Al-Fakih, A. (Elsevier Ltd, 2021)
CFRP is an alternative technique for cracking control of high-chloride reinforced concrete (RC) beams. This research, therefore, investigates the strength performance and failure mode and cracking behaviour of RC beams incorporated with sea sand bonded externally with the carbon fibre reinforced polymer (CFRP) plate. Sea sand is used as a 100 replacement of fine aggregate. Three batches of RC beams were carried out in this research, including the control beam (no sea sand neither CFRP), RC beam with normal sand bonded with CFRP plate, and RC beam with sea sand and bonded with CFRP. A four-point bending test was performed under static loading for the specimens. Finite element simulation was modelled for further comparison. The experimental findings showed that the flexural capacity of the sea sand RC beam bonded externally with CFRP plate is 5.50 greater than the flexural strength of the beam without CFRP (control beam). Besides, results demonstrated that RC beams bonded externally with CFRP were failed by plate end debonding (PED) while the control RC beam without bonding was failed at the mid-span by concrete crushing. However, the bonded RC beams were stiffer, which could lead to lower crack spacing. Finite element simulation showed very acceptable results compared to the experimental results. Â© 2021 Institution of Structural Engineers